Application of the PET ligand [C-11]ORM-13070 to examine receptor occupancy by the alpha(2C)-adrenoceptor antagonist ORM-12741: translational validation of target engagement in rat and human brain - Shahid Mohammed; Rinne Juha O; Scheinin Mika; Virta Jere; Marjamäki Päivi; Solin Olof; Arponen Eveliina; Sallinen Jukka; Kuokkanen Katja; Rouru Juha (SPRINGER, 2022)
Background
Availability of the α2C-adrenoceptor (α2C-AR) positron emission tomography (PET) tracer, [11C]ORM-13070, and the α2C-AR antagonist ORM-12741 allows probing of the roles of this G-protein coupled receptor subtype in brain function, both in healthy humans and in patients with various brain disorders. This translational study employed [11C]ORM-13070 autoradiography and PET to determine α2C-AR occupancy by ORM-12741 in rat and human brain, respectively.
Results
ORM-12741 has high affinity (Ki: 0.08 nM) and potent antagonist activity (Kb: 0.04 nM) as well as selectivity (Ki estimates for the humanα2A-AR and α2B-AR were 8.3 nM and 0.8 nM, respectively) for the human α2C-AR subtype. [11C]ORM-13070 had highest uptake in the basal ganglia of rat and human brain. Pretreatment with ORM-12741 inhibited [11C]ORM-13070 binding in rat striatum in a time- and dose-dependent manner at 10 and 50 µg/kg (s.c.) with an EC50 estimate of 1.42 ng/mL in rat plasma, corresponding to protein-free drug concentration of 0.23 nM. In the living human brain, time- and dose-related α2C-AR occupancy was detected with EC50 estimates of 24 ng/mL and 31 ng/mL for the caudate nucleus and putamen, respectively, corresponding to protein-free concentrations in plasma of 0.07 nM and 0.1 nM. Modelling-based maximum α2C-AR occupancy estimates were 63% and 52% in the caudate nucleus and the putamen, respectively.
Conclusions
ORM-12741 is a selective α2C-AR antagonist which penetrates the rat and human brain to occupy α2C-ARs in a manner consistent with its receptor pharmacology.
Trial registration number and date of registration: ClinicalTrial.cov NCT00829907. Registered 11 December 2008. https://clinicaltrials.gov/.